Biopsychosocial Determinants of Quality of Life in Patients with Hepatitis B and C: Quality of Life in Patients with Hepatitis B and C - Kazmi, Syed Messum Ali; Iftikhar, Rabia (Pakistan Journal of Health Sciences, 2023)
Hepatitis B and C are highly contagious viral diseases that impact the liver. Past research findings have identified that in addition to the physical burden of disease, there are numerous psychopathological consequences of these diseases including depression, anxiety, stress and other psychiatric comorbidities. Objectives: To assess the prevalence of psychiatric comorbidities in patients, perceived immune status, social support, resilience, health and physical lifestyle and the predictive role of these factors in impacting quality of life in patients with Hepatitis B and C. Methods: a correlational research design was used with an independently drawn sample of 400 participants (196 with chronic HBV and 204 with chronic HCV) with the mean age of 40.8 years and a balanced gender distribution. The sample size was finalized using G power analysis with 95 % confidence intervals. Normality checks were also performed on the data through assessing skewness, kurtosis and shape of the distribution. Cross Cutting Symptoms Measure, Essential Resilience Scale, Immune Status Questionnaire, Health and Life Style Scale and WHO Qol BREF scale were used. Results: The findings showed that cross cutting symptoms (depression, anger, anxiety, somatic symptoms, suicidal ideation, psychosis, sleep problems, memory, repetitive thoughts and behaviors, dissociation, personality functioning, substance abuse) had a significant negative predictive association with health and lifestyle, perceived immune status, resilience. Conclusions: It has been assessed that cross cutting symptoms, perceived immune status, health and lifestyle factors, social support and resilience significantly impact quality of life.